Pengolahan Air Limbah Betalaktam Menggunakan Reagen Kaporit, PAC, dan Alum Sulfat - Gede H. Cahyana; Gilang Gumilar; Tri Mulyani (Fakultas Teknik, 2021)
Beta lactam antibiotics are pollutant in water bodies such as lakes and rivers. Beta lactam rings may have a negative impact on living beings in lakes and rivers. Beta lactam rings also cause resistance or bacterial resistance to antibiotics. If human beings are exposed to beta lactam ring, this could negatively impact on their health. This study attempted to break down the beta lactam rings with several chemical reagents. These reagents hydrolyze the beta lactam ring and are then analyzed using the HPLC (High Performance Liquid Chromatography) instrument. This study aims to determine the how effective the reagent for breaking the beta lactam ring. The research was conducted in three stages: preliminary research, research on reagent effectiveness , and research on β-lactamase degradation using reagents. The results showed that calcium hypochlorite was able to break the beta lactam cycle with 100% efficiency.